THE USE OF TECHNOLOGY IN ISLAMIC RELIGIOUS EDUCATION: DIGITAL INCLUSION IN THE SOCIETY 5.0 ERA - Alya Kamilin; Muhammad Solekhin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
In the world of education, technology is very influential in facilitating all educational activities. The existence of this educational technology can maximize the teaching and learning process, besides that technology can also be called a complement in teaching and learning activities. The presence of technology in Islamic Religious Education learning also enriches a more flexible learning experience. Learning is no longer limited to formal classrooms, but can be done anytime and anywhere. The research method used in this study is qualitative research with a case study approach. A case study is an exploration of